The Supremacy Of Law In Human Rights Enforcement (A Solution To Settlement Of Human Rights Violations) - Miftah Idris; Abdul Maasba Magassing (International Journal of Education, Vocational and Social Science, 2023)
Despite the importance of human rights, violations of these rights continue to be widespread throughout the world. These violations can take many forms, including torture, discrimination, arbitrary detention, and restrictions on freedom of expression and assembly. Addressing these violations and promoting respect for human rights requires a multi-faceted approach, including legal protection, advocacy, education, and social and economic development. In solving the problems under study, the research method used is normative legal research with secondary data types which are analyzed in several ways to obtain qualitative research results. The research results show that the legal system plays an important role in upholding human rights and promoting accountability for those who violate them. Legal frameworks provide important protections for human rights, both domestically and internationally, and the judiciary serves as a key mechanism for upholding these protections. Potential solutions to improve the enforcement of human rights include increasing public awareness and education about human rights, strengthening the independence and capacity of the judiciary, and promoting international cooperation and collaboration in the enforcement of human rights.